2019
DOI: 10.1155/2019/1349509
|View full text |Cite
|
Sign up to set email alerts
|

Knowing Your Beans in Parkinson’s Disease: A Critical Assessment of Current Knowledge about Different Beans and Their Compounds in the Treatment of Parkinson’s Disease and in Animal Models

Abstract: This review contains a critical appraisal of current knowledge about the use of beans in both animal models and patients with Parkinson's disease (PD). The potential beneficial effects of beans in PD are increasingly being touted, not only in scientific journals but also by the lay media. While there is a long tradition in Ayurvedic medicine of prescribing extracts from Mucuna pruriens (MP), whose seeds contain 5% L-3,4-dihydroxyphenylalanin (L-DOPA), many other beans also contain L-DOPA (broad beans, common b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 84 publications
0
8
0
2
Order By: Relevance
“…Likewise, the potential of Mucuna seed powder extract significantly improved activity of brain mitochondrial complex-I without disturbing total monoamine oxidase activity in vitro [61]. Mucuna pruriens also has the potential to amend immune components like tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), interferon-λ (IFN-λ), interleukin-1β (IL-1β), inducible nitric oxide synthase (iNOS), and interleukin-2 (IL-2) in the central nervous system, thereby, averting the progression of dopaminergic neurons degeneration, in PD [62]. Moreover M. pruriens was also assessed for levodopa pharmacokinetics by Sarrafchi et al, in a double-blinded clinical and pharmacological study.…”
Section: Zebra Fish (Danio Rerio)mentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the potential of Mucuna seed powder extract significantly improved activity of brain mitochondrial complex-I without disturbing total monoamine oxidase activity in vitro [61]. Mucuna pruriens also has the potential to amend immune components like tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), interferon-λ (IFN-λ), interleukin-1β (IL-1β), inducible nitric oxide synthase (iNOS), and interleukin-2 (IL-2) in the central nervous system, thereby, averting the progression of dopaminergic neurons degeneration, in PD [62]. Moreover M. pruriens was also assessed for levodopa pharmacokinetics by Sarrafchi et al, in a double-blinded clinical and pharmacological study.…”
Section: Zebra Fish (Danio Rerio)mentioning
confidence: 99%
“…Copious studies have scrutinized the effect of MP in PD patients. The bioavailability of L-DOPA in the central nervous system is about one-fifth when pooled with carbidopa or benserazide due to nonexistence of DOPA decarboxylase inhibitor (DDCI) in Mucuna [61][62][63][64][65]. Even then, the first report in 1978 revealed that 23 PD patients were treated with MP with similar effect and better tolerance than L-DOPA/benserazide.…”
Section: Human Trialsmentioning
confidence: 99%
“…В-третьих, животные не страдают от болезни Паркинсона в дикой природе. Животные модели данного заболевания основаны на генетических мутациях или токсин-индуцированном паркинсонизме, и, следовательно, полученные данные не обязательно применимы к медленно прогрессирующему нейродегенеративному заболеванию у людей [35]. [37].…”
Section: экспериментальные работы на животныхunclassified
“…С 2019 г. проводится многоцентровое международное рандомизированное клиническое исследование, посвященное определению эффективности порошка Mucuna pruriens в сравнении с коммерческими таблетками леводопа/бензеразид 200/50 мг в долгосрочной перспективе у пациентов с недавно диагностированным паркинсонизмом на ранней стадии заболевания (Панафриканский реестр клинических испытаний, номер 201611001882367) [35].…”
Section: результаты клинических исследованийunclassified
“…9 The legumes have known to provide with the symptomatic ease, as the family is known to possess L-DOPA or Levodopa in a varying amount which is a majorly used treatment to assess PD symptoms and the presence of secondary metabolites known to decrease oxidative stress. Beans like Mucuna pruriens (L-DOPA-1%), Vivia faba (L-DOPA-0.5%), Phaseolus vulgaris (L-DOPA-0.25%) exhibit neuroprotective effect considered to be due to the presence of levodopa and various antioxidants 10 . In this study, we will be examining Cyamopsis tetragonoloba for its Anti-parkinson's activity through in-vivo biochemical and behavioral studies on albino rats.…”
Section: Introductionmentioning
confidence: 99%